Leaf extract from Costus pictus D.: Unveiling the power of synthesized TiO2 nanoparticles through phytochemical analysis and exciting Antiplatelet and Anticoagulant activity evaluations - KR, Shalini; R, Udayakumar; S, Udhayan (Journal of Neonatal Surgery, 2025)
The environmentally friendly synthesis of titanium dioxide (TiO2) nanoparticles (NPs) utilizing the leaf extract of Costus pictus D. was accomplished to create sustainable and biologically active materials. This research involves the synthesis, characterization, and assessment of these nanoparticles’ anticoagulant and antiplatelet properties. Various characterization methods, such as X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and Gas chromatography-masscrystalline nanoparticles enriched with bioactive compounds sourced from the plant extract. The synthesized TiO2 nanoparticles demonstrated significant anticoagulant properties by by markedly prolonging clotting times and inhibiting intrinsic coagulation pathways. Additionally, these nanoparticles exhibited strong dose-dependent antiplatelet activity, showing superior efficacy compared to aspirin in inhibiting ADP-induced platelet aggregation. These findings underscore the potential therapeutic applications of Costus pictus- mediated TiO2 nanoparticles in advancing cardiovascular health management. The study also emphasizes the importance of green synthesis as a sustainable and environmentally responsible methodology for developing nanoparticles in biomedical applications, highlighting the responsibility of researchers in the field.